2017
DOI: 10.1080/15391523.2017.1388200
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Laptop Use by Children in a Southern Country: A Mixed-Method Approach

Abstract: International audienceInformation and communication technology (ICT) use among children in low-income countries remains understudied. The purpose of this study is to describe laptop usage among children in 10 the context of the One Laptop per Child (OLPC) project 4 years after the laptops were first introduced in a community in Madagascar. The study was conducted using a mixed-method approach combining analysis of ICT use history, empirical observations, and interviews with children and parents. In class, acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Children's use of ICT at home in RCC is understudied [40]. Research shows that family support is a predictor of computer use, and that family members act as mediators to appropriate technologies [40], [41].…”
Section: Technology Use Outside the Classroom In Rccmentioning
confidence: 99%
See 3 more Smart Citations
“…Children's use of ICT at home in RCC is understudied [40]. Research shows that family support is a predictor of computer use, and that family members act as mediators to appropriate technologies [40], [41].…”
Section: Technology Use Outside the Classroom In Rccmentioning
confidence: 99%
“…Children's use of ICT at home in RCC is understudied [40]. Research shows that family support is a predictor of computer use, and that family members act as mediators to appropriate technologies [40], [41]. Nogry [40] examined computer use in a village in Madagascar that was involved in an OLPC project for four years.…”
Section: Technology Use Outside the Classroom In Rccmentioning
confidence: 99%
See 2 more Smart Citations
“…The context of the educational system shapes how students used the devices. For example, primary students in Madagascar used their devices at school mainly as a textbook and rarely used them for production or other uses (Nogry & Varly, 2017); when students from Cyprus used the devices as a research tool they did not combine this use with other uses (Zacharia et al, 2016). Studies conducted in New Zealand reported similar uses found in the current study, such as using for communication, production, seeking information, and as a research tool (Falloon, 2015(Falloon, , 2017a(Falloon, , 2017b.…”
Section: Context Events and Historymentioning
confidence: 51%